Implementation Of Akhlakul Karimah Values In Establishing Educators With Prophetic Character In Madrasah Tsanawiyah - Pratama, Irja Putra; Purnomo, Eko; Hidayat, Muslih (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study aimed to determine the implementation of Akhlakul Karima's values in forming educators with prophetic character at MTs IV Ahliyah Palembang in producing quality educators. The research methods used are observation, interviews, and documentation. Data analysis techniques include data condensation, data presentation, and conclusions. The research results obtained are that efforts to produce quality educators are implemented by forming educators with prophetic character with the soul of mu'addib (educator), mujahid (fighter), mujaddid (reformer), and mujahid (unifier). Educators with prophetic nature are personalities possessed by prophets and apostles, through prophetic character so that they become educators with a prophetic spirit who are successful in being good role models and increasing actions that are by the values of akhlaqul karimah.